2020
DOI: 10.1038/s41598-020-67806-9
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: A Randomised Controlled Trial on the Effectiveness and Adherence of Modified Alternate-day Calorie Restriction in Improving Activity of Non-Alcoholic Fatty Liver Disease

Abstract: An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Respectively, of the 30 included studies, 27 used a parallel group design, and 3 used a crossover design. These studies were conducted in the United States [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], Germany [ 43 , 44 ], Malaysia [ 45 , 46 , 47 ], China [ 48 , 49 ], the United Kingdom [ 50 ], Norway [ 51 ], Sweden [ 52 ], Poland [ 53 ], Korea [ 54 ], and Austria [ 55 ]. Of the total extracted studies, 10 were CR interventions, 12 were IF interventions, and 8 combined and/or compared both IF and CR.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Respectively, of the 30 included studies, 27 used a parallel group design, and 3 used a crossover design. These studies were conducted in the United States [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], Germany [ 43 , 44 ], Malaysia [ 45 , 46 , 47 ], China [ 48 , 49 ], the United Kingdom [ 50 ], Norway [ 51 ], Sweden [ 52 ], Poland [ 53 ], Korea [ 54 ], and Austria [ 55 ]. Of the total extracted studies, 10 were CR interventions, 12 were IF interventions, and 8 combined and/or compared both IF and CR.…”
Section: Resultsmentioning
confidence: 99%
“…Of the total extracted studies, 10 were CR interventions, 12 were IF interventions, and 8 combined and/or compared both IF and CR. In relation to study length, 1 study was short-term (i.e., ≤4 weeks) [ 55 ], 14 medium-term (4–12 weeks) [ 27 , 28 , 31 , 36 , 39 , 45 , 46 , 47 , 48 , 49 , 51 , 52 , 53 , 54 ], and 15 longer-term (>12 weeks) [ 26 , 29 , 30 , 32 , 33 , 34 , 35 , 37 , 38 , 40 , 41 , 42 , 43 , 44 , 50 ]. Populations assessed included healthy men [ 45 , 46 ], healthy individuals [ 28 , 31 , 39 ], healthy non-obese individuals [ 29 , 33 , 34 , 35 , 55 ], healthy sedentary individuals [ 40 ], obese/overweight individuals [ 26 , 30 , 38 , 41 , 42 , 49 , 50 , ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two relevant trials [ 71 , 72 ] evaluated alternated-day fasting and established an association of these intermitted fasting methods with a reduction in liver fat and fibrosis score. Finally, a recent meta-analysis, with 417 NAFLD participants from six trials, showed the positive effects of intermittent fasting on liver tests [ 73 ].…”
Section: Nutritional Treatment In Nafldmentioning
confidence: 99%